2007
DOI: 10.1016/j.jsat.2006.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Readiness for Change and opinions toward treatment innovations

Abstract: Program administrators and staff in treatment programs participating in the National Drug Abuse Treatment Clinical Trials Network (CTN) completed surveys to characterize participating programs and practitioners. A two-level random effects regression model assessed the influence of Organizational Readiness for Change (ORC) and organizational attributes on opinions toward the use of four evidence-based practices (manualized treatments, medication, integrated mental health services, and motivational incentives) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 17 publications
7
95
0
Order By: Relevance
“…Findings on whether supervisor or staff attitudes about EBP implementation vary by the type of treatment unit within which the respondent works are mixed. McCarty et al (2007) and Fuller et al (2007) did not find treatment unit to be associated with differences in staff attitudes regarding EBPs. However, in a study of 376 counselors and 1,083 clients involved in methadone, residential and outpatient substance abuse programs in Oregon and Massachusetts, Rieckmann et al (2007) reported that the most consistent support for pharmacological therapies was from staff in outpatient settings.…”
Section: Control Factorsmentioning
confidence: 76%
See 2 more Smart Citations
“…Findings on whether supervisor or staff attitudes about EBP implementation vary by the type of treatment unit within which the respondent works are mixed. McCarty et al (2007) and Fuller et al (2007) did not find treatment unit to be associated with differences in staff attitudes regarding EBPs. However, in a study of 376 counselors and 1,083 clients involved in methadone, residential and outpatient substance abuse programs in Oregon and Massachusetts, Rieckmann et al (2007) reported that the most consistent support for pharmacological therapies was from staff in outpatient settings.…”
Section: Control Factorsmentioning
confidence: 76%
“…The Simpson and Flynn (2007) Organizational Readiness for Change model and the Texas Christian University Organizational Readiness for Change scales (TCU ORCstaff, TCU ORC-director; Lehman, Greener, & Simpson, 2002) have been used in prior addictions treatment research efforts to understand staff attitudes toward EBPs (see, for example, Fuller et al, 2007;Lundgren et al, 2011;Lundgren, Krull, Zerden, & McCarty, 2011). These articles indicate that specific aspects of organizational capacity are associated with more positive staff attitudes toward EBPs.…”
Section: Organizational Capacity and Implementation Of Evidence-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of these skewed percentages and the lack of client documentation prevented us from linking the level of organizational functioning with rates of client retention. Fuller et al (2007) consider that the long-term survival of a substance abuse treatment facility requires the understanding and comprehension of its organizational capacities to respond to external and internal pressures for change. In South Africa it is evident that the realm of substance abuse treatment is faced with a plethora of external and internal pressures for change and that the successful transfer of evidence-based innovations to real-world applications to meet these pressures for change will require careful planning, implementation, and on-going evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the ORC responses between program directors and counselors appear to be consistent with their respective roles and responsibilities, and can be an important factor in assessing the overall functioning of a program (Fuller et al 2007;Lehman et al 2002).…”
mentioning
confidence: 94%